Faktor-Faktor Yang Mempengaruhi Kinerja Perawat Di Ruang Rawat Inap Dewasa Rumah Sakit Medistra Jakarta: Factors that Influence the Performance of Nurses in the Adult Inpatient Room at Medistra Hospital, Jakarta - Setiawati, Eka (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Nurse performance is the result of work in quality and quantity achieved by a nurse in carrying out her duties in accordance with the responsibilities given. Inpatient services are services for patients admitted to hospitals who occupy care beds for the purposes of observation, diagnosis, therapy, medical rehabilitation and or other medical services. This study aims to determine the factors of work motivation, job satisfaction and leadership style that influence the performance of executive nurses in adult inpatient rooms at Medistra Hospital, Jakarta. Methods: This type of research is a quantitative study the population of this research is all nurses who are in the adult inpatient room of the Medistra Hospital, Jakarta totaling 80 people. Analysis using statistical tests with a significance level (α); 0.05 statistical test used is the chi-square test.    Results: The results showed that work motivation (p = 0,00); job satisfaction (p = 0,00); and leadership style (p = 0,00) affected the performance of nurses at Medistra Hospital, Jakarta. Discussion: Work motivation, job satisfaction and leadership style affect nurse performance. This shows that work motivation, job satisfaction and leadership style have a major influence on the performance of nurses at Medistra Hospital, Jakarta. To create quality nurses a strong push from the hospital is needed.